Aptamer-Gated Nanoparticles for Smart Drug Delivery - Huseyin Avni Oktem; Fusun Eyidogan; Veli Cengiz Ozalp (MDPI AG, 2011)
Aptamers are functional nucleic acid sequences which can bind specific targets. An artificial combinatorial methodology can identify aptamer sequences for any target molecule, from ions to whole cells. Drug delivery systems seek to increase efficacy and reduce side-effects by concentrating the therapeutic agents at specific disease sites in the body. This is generally achieved by specific targeting of inactivated drug molecules. Aptamers which can bind to various cancer cell types selectively and with high affinity have been exploited in a variety of drug delivery systems for therapeutic purposes. Recent progress in selection of cell-specific aptamers has provided new opportunities in targeted drug delivery. Especially functionalization of nanoparticles with such aptamers has drawn major attention in the biosensor and biomedical areas. Moreover, nucleic acids are recognized as an attractive building materials in nanomachines because of their unique molecular recognition properties and structural features. A active controlled delivery of drugs once targeted to a disease site is a major research challenge. Stimuli-responsive gating is one way of achieving controlled release of nanoparticle cargoes. Recent reports incorporate the structural properties of aptamers in controlled release systems of drug delivering nanoparticles. In this review, the strategies for using functional nucleic acids in creating smart drug delivery devices will be explained. The main focus will be on aptamer-incorporated nanoparticle systems for drug delivery purposes in order to assess the future potential of aptamers in the therapeutic area. Special emphasis will be given to the very recent progress in controlled drug release based on molecular gating achieved with aptamers.